Magnitude and Sources of Sediment Input to the Mackenzie Delta, Northwest Territories, 1974-94 - Carson, M.A.; Jasper, J.N.; Conly, F.M. (ARCTIC, 1998)
Hydrometric and sediment data collected by Environment Canada in the Mackenzie Basin during the period 1974-94 have been analyzed to produce detailed estimates of sediment inputs to the Mackenzie Delta, based largely on sediment rating equations. The mean annual sediment supply to the delta is determined as 128 million tonnes (Mt), of which about 4 Mt is sandy bed material moved in by the Mackenzie River itself. Virtually all of this sediment (more than 99%) is supplied to the delta during the May-October period, the peak months being May (27%), June (36%), and July (19%). About 17% of the fine-sediment load is supplied by the Peel River; the rest is delivered by the Mackenzie. The largest single contributor to the Mackenzie River wash load (103 Mt) is the Liard River (41 Mt). The preliminary estimate of the contribution of the other west-bank tributaries, in combination, is about 36 Mt, though this figure is probably too low. The precision of these estimates using the sediment rating approach (compared to time-integration during months with reasonable sampling frequency) is about 10% for the mean monthly sediment loads and about 5% for the mean annual sediment load during the 1974-94 period. The absolute accuracy of sediment load estimates is more difficult to assess because published flow data for delta inflow stations are acknowledged to be much less reliable for the spring breakup period than for other times of the year. On a procédé à l'analyse de données hydrométriques et sédimentaires recueillies par Environnement Canada dans le bassin du Mackenzie de 1974 à 1994 afin d'obtenir une estimation détaillée de l'apport solide au delta du Mackenzie, en se fondant en grande partie sur des équations de calibrage des sédiments. L'apport sédimentaire annuel moyen au delta est évalué à 128 millions de tonnes (Mt), dont 4 Mt environ consistent en matériaux sableux charriés par le fleuve lui-même. La majorité de l'apport de ces sédiments (plus de 99 p. cent) au delta a lieu durant la période allant de mai à octobre, ...